2022
DOI: 10.3390/ijms232012330
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin Proteasome Gene Signatures in Ependymoma Molecular Subtypes

Abstract: The ubiquitin proteasome system (UPS) is critically important for cellular homeostasis and affects virtually all key functions in normal and neoplastic cells. Currently, a comprehensive review of the role of the UPS in ependymoma (EPN) brain tumors is lacking but may provide valuable new information on cellular networks specific to different EPN subtypes and reveal future therapeutic targets. We have reviewed publicly available EPN gene transcription datasets encoding components of the UPS pathway. Reactome an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 140 publications
0
2
0
Order By: Relevance
“…Another explanation for why elevated CDC20 levels promote cancer progression is that CDC20 accumulation reflects compromised APC activity, and is not therefore able to target CDC20 (or its other targets) for degradation, which is consistent with the overabundance of multiple APC substrates observed in unrelated cancer tissues. While CDC20 may be pro-oncogenic, it is unlikely to act in isolation, as at least 60 of the known 69 human APC substrates are associated with multiple cancer types when they accumulate [20], and are now considered a cancer signature [73,74]. A recent series of papers found that APC substrate-mRNAs, including HURP and CDC20, are elevated in multiple cancers, and are now recognized as a hub or signature gene set predictive of poor prognosis cancer (a subset of references are included here; [75][76][77][78]).…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for why elevated CDC20 levels promote cancer progression is that CDC20 accumulation reflects compromised APC activity, and is not therefore able to target CDC20 (or its other targets) for degradation, which is consistent with the overabundance of multiple APC substrates observed in unrelated cancer tissues. While CDC20 may be pro-oncogenic, it is unlikely to act in isolation, as at least 60 of the known 69 human APC substrates are associated with multiple cancer types when they accumulate [20], and are now considered a cancer signature [73,74]. A recent series of papers found that APC substrate-mRNAs, including HURP and CDC20, are elevated in multiple cancers, and are now recognized as a hub or signature gene set predictive of poor prognosis cancer (a subset of references are included here; [75][76][77][78]).…”
Section: Discussionmentioning
confidence: 99%
“…Although these responses may initially be engaged to aid cellular stress adaptation, cancer cells usurp and/or co-opt these pathways for their benefit in numerous ways. We recently identified distinct gene expression changes in ubiquitin ligases and ligase adaptors in different human brain tumors and subtypes [42,43]. Sustained UPR signaling has been reported in diverse cancers, including breast, prostate, and brain cancers, and emerging evidence links ERAD and UPR to an array of pro-tumorigenic processes, including angiogenesis, metastasis, and cancer stem cell expansion [38].…”
Section: Introductionmentioning
confidence: 99%